A study of congenital anomalies in a tertiary care hospital in North East region, India - Devi, Kangjam Radhesana; Devi, R. K. Praneshwari; Priya, Jyoti; Sanaton, Ahanthembi; Singh, Leimapokpam Roshan; Murray, Lalhlimpuii (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Congenital anomalies are important cause of morbidity and mortality in newborns and are defined as structural and functional abnormalities including metabolic disorders present at birth. These defects are of prenatal origin resulting from defective embryogenesis or intrinsic abnormalities in the process of development and are associated with various risk factors. Methods: Our study is a cross-sectional study done at Regional Institute of Medical Sciences, Imphal over period of one and half years from May 2016 to October 2017. Aim of study was to find out incidence of congenital anomalies and proportions of different types of congenital anomalies. Outcome was studied in relation to maternal age, religion, parity, gestational age, sex of baby, outcome and birth weight of baby. Results: Total numbers of congenital anomalies were 91 out of 13658 births. Incidence of congenital anomalies was 0.66%. Most common congenital anomaly was cleft lip (17.6%) followed by CTEV (13.2%) and was more common among male term babies. These were most common in 18-24 years of maternal age group (34.1%) followed by 30-34 years (26.4%) and among women of parity P0-P2. Conclusions: Congenital malformations are a major cause of still births and infant mortality. A level II targeted scan should be done at 18-20 weeks to find out anomalies and reduce the prevalence. There should be widespread education in the community regarding the common congenital malformations, their outcomes and possible available modes of treatment.